2019
DOI: 10.1016/j.afos.2019.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of fragility fracture and low bone mineral density in patients with a history of parental fracture

Abstract: Objectives Bone mineral density (BMD) and fragility fracture (FF) have high heritability, but few data exist on impact of other factors on families with fracture history. We aimed to evaluate predictors of FF and low BMD, in patients with family history of FF. Methods This was a retrospective study on patients undergoing dual energy X-ray absorptiometry at a district general hospital (DGH), 2004–2016. Parameters recorded (in addition to standard dual energy X-ray absorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
0
7
1
Order By: Relevance
“…This is similar to what is reported in another study. 31 In our study it was however not statistically significant (p>0.05). The waist circumference demonstrated a positive correlation with mean serum PINP (Table 3).…”
Section: Variablescontrasting
confidence: 69%
“…This is similar to what is reported in another study. 31 In our study it was however not statistically significant (p>0.05). The waist circumference demonstrated a positive correlation with mean serum PINP (Table 3).…”
Section: Variablescontrasting
confidence: 69%
“…Most of the associations found in our study, except with diabetes, were similar to those consistently associated with BMD as measured with DEXA scans. [6][7][8][9][10][11][12][13][14][15] Diabetes and bone strength depends on the type of diabetes, T1DM presenting with decreased BMD while patients with T2DM presenting with normal to increased BMD. 22,23 Our study, which included T1DM and T2DM in a single group, showed decrease in BMD as an association to diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that one out of two women and one out of four men at the age of 50 years and older will face at least one osteoporotic fracture (2) . Among the factors which seem to lead to lower bone mineral density (BMD) and increased risk of fracture are genetic background, lack of exercise, high body fat mass, smoking, high alcohol intake and prolonged use of glucocorticoids (3)(4)(5) . On the other hand, physical exercise (in particular weight-bearing exercise and walking), starting early before menopause onset, seems to be beneficial for the maintenance or increase of BMD (6,7) .…”
mentioning
confidence: 99%